Association of Red Cell Distribution with Angiographic Severity of Coronary Artery Disease Assessed by SYNTAX Score in Non-ST Elevation Myocardial Infarction (Cardiovascular Journal, 2021)
Background: Red cell distribution width is a simple measure of red cell size heterogeneity (i.e., anisocytosis) in peripheral blood measured by hematology auto analyzer and has been shown to be a predictor of poor outcomes in various cardiovascular conditions including coronary artery disease (CAD). The present study was intended to find the association between RDW-CV and severity of CAD in NSTEMI patients.Methods: The present cross-sectional analytical study was carried out in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh, from June 2018 to July 2019. A total of 70 NSTEMI patients undergoing coronary angiogram during the index hospitalization were included in the study. They were divided into two groups on the basis of RDW-CV (Group-I RDW-CV